Myocardial Imaging with Thallium-201: Subtraction Imaging with 201TlCl and 99mTcO4- for the Visualization of the Right Ventricle - YANO, Kesato; MIYAZAWA, Masanori; TAKIZAWA, Masaomi; FUJII, Tadashige; HANDA, Kenjiro; KUSAMA, Shozo; KANAI, Hisakata; HIRAYAMA, Jiro (RADIOISOTOPES, 1979)
The dual radioisotope techniques with 201TlCl and 99mTcO4- were performed in 30 cases inclusive of various heart and lung diseases, using a scintillation camera coupling to a small digital computer. The scintigraphic procedures were started about 5 minutes after intravenous injection of 201TlCl. The myocardial images such as anterior, 60°left anterior oblique, and left lateral view, were obtained. Next, 30°left anterior oblique view was taken and radionuclide angiogram with 99mTcO4- was done in the same position too. This joint use of the myocardial imaging and radionuclide angiography could increase diagnostic reliability. Superimposing the image as iso-count map extracted out of radionuclide angiogram to the brightness image of 201TlCl, the anatomic orientation of the image of 201TlCl was improved. Subtracting the blood pool image with 99mTcO4- or radionuclide angiogram, which showed visualization of the right ventricle, lungs and left ventricle, from the image of 201TlCl, the subtraction image was obtained. The right ventricle was visualized more clearly on this subtraction image than the original image of 201TlCl. Good visualization of the right ventricle was shown in 25 cases on the subtraction image, and in 17 cases on the original image of 201TlCl.